Factors Affecting the Behavior of University Community to Use Credit Card - Sari, Maya; Rofaida, Rofi (Universitas Prasetiya Mulya, 2011)
This study was aimed to gain insights and tested the factors that influence credit cards usage in university community of UPI through Theory of Planned Behavior model approach. Using Path Analysis to explain the direct and indirect influence of attitude, subjective norm and behavioral control to intention and behavior of credit card usage. The results showed all respondents have a positive attitude towards credit cards usage, with high influence of subjective norm, high behavior control, high intention to use credit cards and all respondents used credit cards wisely. There was positive and significant effect either simultaneously or partially between behavioral attitudes, subjective norms, and behavior control toward the intention to use credit card. The partial test results showed behavioral attitude has the greatest influence on the intention to use credit card. There was a positive and significant influence both simultaneously and partially between behavioral attitudes, subjective norms, and behavioral control on default-risk debt behavior. The partial results showed that attitude gives the greatest influence on default debt risk behavior. The result also proved there was a positive and significant influence of the intention to use credit card on default debt risk behavior.